The Distinction of Peace A Social Analysis of Peacebuilding - Goetze, Catherine (Configurations: Critical Studies of World Politics, 2016)
"Peacebuilding" serves as a catch-all term to describe efforts by an array of international organizations, nongovernmental organizations, and agencies of foreign states to restore or construct a peaceful society in the wake-or even in the midst-of conflict. Despite this variety, practitioners consider themselves members of a global profession. In The Distinction of Peace, Catherine Goetze investigates the genesis of peacebuilding as a professional field of expertise since the 1960s, its increasing influence, and the ways it reflects global power structures. Goetze describes how the peacebuilding field came into being, how it defines who belongs to it and who does not, and what kind of group culture it has generated. Using an innovative methodology, she investigates the motivations of individuals who become peacebuilders, their professional trajectories and networks, and the "good peacebuilder" as an ideal. For many, working in peacebuilding in various ways-as an aid worker on the ground, as a lawyer at the United Nations, or as an academic in a think tank-has become not merely a livelihood, but also a form of participation in world politics. As a field, peacebuilding has developed techniques for incorporating and training new members, yet its internal politics also create the conditions of exclusion that often result in practical failures of the peacebuilding enterprise. By providing a critical account of the social mechanisms that make up the peacebuilding field, Goetze offers deep insights into the workings of Western domination and global inequalities.